(untitled) (Journal of Hama University, 2020)
Introduction: Recently, dentists have become increasingly concerned with the diagnosis of oral lesions. Therefore, it is important to investigate and diagnose early cancer lesions. Some of these oral lesions also have signs of systemic diseases, which can help detect them. Aim: Many of the lesions that affect the facial jugular may be a serious risk factor for the lives of individuals. This research aims to Evaluate the prevalence of tongue lesions in patients visiting the clinics of the Faculty of Dentistry at Damascus university. Materials and Methods: The sample of the study included 300 members of both sexes who were all visitors to the clinics of the Faculty of Dentistry at the University of Damascus 2018, and ranged between 6 and 82 years. Results: As a result, the number of casualties was (50 in 158 males) (28 in 142 females) with a total of 78 out of a total of 300 individuals, 26.0% of the total sample size. The distribution was as follows: (fissured tongue as 44.9%, hairy tongue individuals as 25.6%, geographic tongue as 14.1%, macroglossia as 3.8%, ankyloglossia by 2,6% , median rhomboid glossitis as 1,3% , varicose as 1,3% , furred tongue as 1,3% , high frenum as 1,3% , geographic and fissured as 2,6% , hairy and fissured tongue as 1,3%. Conclusion: under the limitation of this study, it can be concluded that: • The prevalence of tongue lesions in this study was 26.0% of the total sample, which is considered a relatively large percentage. • the most relevant tongue lesion is fissured tongue. It was found that males are more likely to develop tongue lesions than females.